WARNA LOKAL TEKS AMIR HAMZAH DALAM SERAT MENAK - Kun Zachrun Istanti (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2006)
The receptive analysis of the Hikayat Amir Hamzah (HAH) text shows active response from the readers through the creation of new text such as Serat Menak (Sr.Mn.). The relationship between both of them can be seen in its adaptations into Javanese literature (Sr.Mn.) in which HAH undergoes some changes. The author adjusted HAH to suit the Javanese literary and cultural traditions, e.g. Sr.Mn. is composed in the form of tembang (poetry), the name of the characters are adapted into Javanese culture; there are previously unnamed characters which are given names in Sr.Mn.; the history (background) of some characters is made clearly; and more titles (from pewayangan) are attributed to Amir Hamzah and Umar Umayah.